Employment of women in Chinese cultures half the sky (New horizons in management, 2005)
Examining the employment lives of Chinese women living under different government systems at the beginning of the twenty-first century, the contributors to this volume present an overview of factors affecting the employment status of women. The volume includes chapters on the People's Republic of China, Taiwan, Hong Kong and Singapore--nations that have common Chinese cultural experiences but very different economic systems and government structures